Assessment of nutritional status, nutrition related knowledge level and its associated factors among learning disabilities children in special education integration programme (SEIP) in Kota Bharu, Kelantan - Hashim, Nur Hamiza Ruzaini (2020)
Malnutrition has been found to be a common setback among children with learning disability (LD). However, the nutritional status and nutrition related knowledge level among the local LD population are obscure. This study was conducted from April 2016 to June 2017 with the aim to assess the nutrition status, nutrition related knowledge level and its associated factors of LD children studying at Special Education Integration Program (SEIP) in Kota Bharu, Kelantan. Validation and reliability testing was done on the pictorial flipchart questionnaire beforehand. The study involving 99 LD children (37.4% girls and 62.6% boys) at four selected SEIP in Kota Bharu area. Mean (SD) age of study participants were 10.87 (1.55) years. Data on anthropometry, dietary, socio-demography, nutrition related knowledge level and also factors associated were collected using a set of structured questionnaire. The validated nutrition related knowledge questionnaire contained 10 items shows a good reliability with Cronbach Alpha value of 0.60. Most participants are able to identify unhealthy food and minority of them knows which foods are high in calcium. According to the body mass index (BMI) classification, results indicates that the prevalence of 10.1% of LD children (70% boys and 30% girls) who were underweight while 37.3% (62.2% boys and 37.8% girls) were overweight or obese. The mean (SD) score of nutrition related knowledge questionnaire of LD children are 6.07 (2.16). Multiple regression analysis shows that number of siblings (p=0.006), body fat percentage (p<0.001) and feeding problems (p=0.038) were significantly associated with malnutrition among this population. In conclusion, high prevalence of malnutrition are found in this population thus more effective strategies with new interventions programs including improving the nutrition education syllabus at schools to prevent malnutrition from becoming a worldwide problem particularly among children with LD as they face the risk of being left behind.